NMR structure of integrin α4 cytosolic tail and Its interactions with paxillin - Chua, Geok-Lin (2013)
Integrins are a group of transmembrane signaling proteins that are important in biological processes such as cell adhesion, proliferation and migration. Integrins are α/β hetero-dimers and there are 24 different integrins formed by specific combinations of 18 α and 8 β subunits in humans. Generally, each of these subunits has a large extracellular domain, a single pass transmembrane segment and a cytosolic tail (CT). CTs of integrins are important in bidirectional signal transduction and they associate with a large number of intracellular proteins. Principal Findings: Using NMR spectroscopy, we determined the 3-D structure of the full-length α4 CT (Lys968-Asp999) and characterize its interactions with the adaptor protein paxillin. The α4 CT assumes an overall helical structure with a kink in its membrane proximal region. Residues Gln981-Asn997 formed a continuous helical conformation that may be sustained by potential ionic and/or hydrogen bond interactions and packing of aromatic-aliphatic side-chains. 15N-1H HSQC NMR experiments reveal interactions of the α4 CT C-terminal region with a fragment of paxillin (residues G139-K277) that encompassed LD2-LD4 repeats. Residues of these LD repeats including their adjoining linkers showed α4 CT bindinginduced chemical shift changes. Furthermore, NMR studies using LD-containing peptides showed predominant interactions between LD3 and LD4 of paxillin and α4 CT. Docked structures of the α4 CT with these LD repeats suggest possible polar and/or salt-bridge and non-polar packing interactions. Significance: The current study provides molecular insights into the structural diversity of α CTs of integrins and interactions of integrin α4 CT with the adaptor protein paxillin.